Implementasi Corporate Social Responsibility (CSR) Terhadap Peningkatan Kesejahteraan Masyarakat Dalam Perspektif Ekonomi Islam (Studi Kasus Pada PT. Agincourt Resources Kec. Batang Toru Kab. Tapanuli Selatan) - Pakpahan, Rona Melati; Harahap, Nurlaila; Jannah, Nurul (Regress: Journal of Economics & Management, 2022)
This research was conducted to determine the implementation mechanism of the CSR program of PT. Agincourt Resources in improving the welfare of the Kec. Batang Toru, and to find out the impact of implementing the Corporate Social Responsibility (CSR) program carried out by PT. Agincourt Resources Kec. Batang Toru in improving people's welfare in the fields of economy, health, and education is reviewed from the perspective of Islamic Economics which leads to the conclusion whether the implementation of the CSR program has been successfully implemented in accordance with the perspective of Islamic Economics and whether the CSR program can improve the welfare of the community or not. This study uses a qualitative research method with a descriptive approach. The results of the study concluded that in general, PT. Agincourt Resources has succeeded in implementing the CSR program in accordance with the study of the Islamic Economic perspective and is considered to have been able to improve the welfare of the community, this can be seen from the company's Annual Report and Sustainability Report which always reports on the results of every community activity program as well as from several interviews with CSR program recipients. Nevertheless, the company is expected to continuously improve its CSR programs in order to be able to provide the widest possible benefits and be able to create a prosperous and independent community, especially in the Kec. Batang Toru.